Diagnostic Imaging and workup of Malignant Pleural Mesothelioma. - Cardinale, Luciano; Ardissone, Francesco; Gned, Dario; Sverzellati, Nicola; Piacibello, Edoardo; Veltri, Andrea (Acta Biomedica Atenei Parmensis, 2017)
Malignant pleural mesothelioma is the most frequent primary neoplasm of the pleura and its incidence is still increasing.This tumor has a strong association with exposure to occupational or environmental asbestos, often after a long latent period of 30–40 years.Plain chest radiography (CXR) is usually the first-line radiologic examination, but the radiographic findings are nonspecific due to its limited contrast resolution and they need to be complemented by other imaging modalities such as computed tomography (CT), magnetic resonance Imaging (MRI), Positron emission tomography–computed tomography (PET-CT) and ultrasound (US).The aim of this paper is to describe the imaging  features of this malignancy, underlining the peculiarity of CXR, CT, MRI, PET-CT and US and also focusing on diagnostic workup, based on the literature evidence and according to our experience.